ChemInform Abstract: Synthesis of Bicyclic Guanidines via Cascade Hydroamination/Michael Additions of Mono‐N‐acryloylpropargylguanidines. Issue 19 (May 2015) - Kwon, Ki‐Hyeok; Serrano, Catherine M.; Koch, Michael; Barrows, Louis R.; Looper, Ryan E.
Abstract: The yield of the regioselective and scalable reaction sequence marginally depends on the substitution pattern of the substrates.